Keintiman Komunikasi Manusia dan Komputer dalam Film “Her” - Zainuddin Muda Z Monggilo (Jurnal Gama Societa, 2018)
The problem of the research was how the communication intimacy showed in the story of “Her” film. The purpose was to describe the tendency of communication intimacy between human and computer in “Her” film. The film was selected because of its unique and interesting concept and story ideas as well as the series of achievements that have achieved in terms of quality and the advantages of worldwide sales. The sample was 28 sequences with a focus on the sequences contained interactions between Theodore and Samantha as the two main characters. Data were collected through observation, documentation, and literature study with quantitative content analysis method. The research was limited to the manifest function of the research object. The results showed that: (i). The most dominant of communication intimacy in the film was the intimacy at the level of stabilization (56%), followed by affective (19.5%), orientation and exploration (9.8%), and depenetration (4.9%), (ii). The most dominant of communication intimacy featured in the film was an intensive communication (22%), and followed by personal topic (stabilization) (17%), confirmation status (15%), and personal topic (exploration) (10%).Keywords: Communication Intimacy, Computer Technology, Quantitative Content Analysis, “Her” Film